Can emotions be truly group level? evidence regarding four conceptual criteria. [article]. - Smith, Eliot R.
Recent advances in understanding prejudice and intergroup behavior have made clear that emotions help expalin people's reactions to social groups and theie members. Intergroup emotions theory(D. M. Mackie, T. Devos, & E. R. Smith, 2000;., Smith, 2003) holds that intergroup emotions are experienced by individuals when they identify with a social group, making the group part of the psychological self. what differentiates such group-level emotions from emotions that occur purely at the in